HEPATOPROTECTIVE EFFECTS OF POLYHERBAL FORMULATION AGAINST CARBON TETRACHLORIDE-INDUCED HEPATIC INJURY IN ALBINO RATS: A TOXICITY SCREENING APPROACH - Yogi, Bhumika; Mishra, Ashutosh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To investigate the hepatoprotective activity of aqueous methanolic extract of polyherbal formulation and individual extracts of Calotropis procera, Gymnema sylvestre, and Lawsonia inermis leaves. Methods: The hepatoprotective activity of the formulation and extracts were assessed on the basis of histopathological changes in liver of carbon tetrachloride-induced hepatotoxic rats. Results: The result of present studies strongly indicates that the hepatoprotective property of polyherbal formulation as evidenced by less damaged hepatocytes cells. Conclusion: Polyherbal formulation revealed excellent hepatoprotective profile as compared to individual plants due to synergistic effect produced by different phytochemicals present in the formulation. Keywords: Calotropis procera, Gymnema sylvestre, Lawsonia inermis, Carbon tetrachloride.